2017
DOI: 10.1080/02688697.2017.1297368
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of microvascular decompression for hemifacial spasm

Abstract: MVD may be a safe and effective strategy for HFS patients in view of relatively higher cure rates and lower complication risks within follow-up. Besides, patients' age, duration of disease, intraoperative indentation of the REZ of the facial nerve, and disappearance of AMR were the major influential variables may be useful for the prediction of prognosis in the patients underwent MVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Although the surgical outcomes did not differ between the severe- and mild-spasm groups in our study, the degree of indentation and multiple offenders could be important because many previous studies have found these surgical findings to be associated with surgical outcome. 11 12 13 33 Moreover, indentation has been reported to be associated with delayed facial palsy and disease duration, 34 and we also found that HFS severity was independently related to disease duration, indentation degree, multiple offending vessels, and delayed facial palsy. Based on our results, spasm severity could be regarded as a biomarker of the degree of pathologic compression in patients with HFS.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Although the surgical outcomes did not differ between the severe- and mild-spasm groups in our study, the degree of indentation and multiple offenders could be important because many previous studies have found these surgical findings to be associated with surgical outcome. 11 12 13 33 Moreover, indentation has been reported to be associated with delayed facial palsy and disease duration, 34 and we also found that HFS severity was independently related to disease duration, indentation degree, multiple offending vessels, and delayed facial palsy. Based on our results, spasm severity could be regarded as a biomarker of the degree of pathologic compression in patients with HFS.…”
Section: Discussionsupporting
confidence: 70%
“…Although many previous studies have examined predictors of the prognosis of HFS after MVD, they predominantly investigated intraoperative findings rather than clinical features. 10 11 12 13 Unlike previous studies, we focused on the clinical characteristics of HFS. Our reasoning was that the treatment modality should be decided based on both clinical features and intraoperative findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of other cranial neuralgias is lower than that of TN. The prevalence of hemifacial spasm is 0.83 per 100,000 patients and that of glossopharyngeal neuralgia is 0.7 per 100,000 people . Clinical results suggest that the benefit of MVD lasts longer in these neuralgias than in TN as well.…”
Section: Introductionmentioning
confidence: 98%
“…Clinical results suggest that the benefit of MVD lasts longer in these neuralgias than in TN as well. In Japan, 6‐year follow‐up data after MVD for hemifacial spasm showed that 87% of patients continued to have meaningful effects from surgery . Similarly, 12‐year post‐MVD data for treatment of glossopharyngeal neuralgia showed that 28 of 29 patients continued to have lasting treatment effect …”
Section: Introductionmentioning
confidence: 99%